Parenting stress among Malaysian parents of children with Autism Spectrum Disorder (ASD) - Lee, Jun Xin; Ong, SI; Lee, VY; Fairuz Nazri Abdul Rahman, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Autism Spectrum Disorder (ASD) is a neurodevelopmental childhood disorder associated with cognitive and language impairments. Previous research found that children with developmental disorders increase parenting stress but parents of children with ASD, specifically have recorded higher parenting stress than any other developmental disabilities. Hence, this study investigates the difference in parenting stress levels among parents of children with ASD compared to a typical development (TD) control group. Parenting Stress Index, 3rd Edition Short Form was used to assess the parenting stress levels of 30 parents of children with ASD and 36 parents of TD children. Parents of children with ASD were sampled at Universiti Kebangsaan Malaysia Medical Centre (UKMMC), Tangkak Hospital and National Autism Society of Malaysia (NASOM) in Muar and Segamat. Parents of children with ASD recorded significantly higher levels of parenting stress compared to the TD group (p<0.001). Parents of male children of ASD recorded significantly higher levels of parenting stress compared to the parents of male children of TD group (p<0.001). Parents of female children of ASD also recorded significantly higher levels of parenting stress compared to parents of female children of TD group (p<0.001). Intervention towards ASD children should not only focus on minimizing the core symptoms but should also pay attention to the family’s mental health as well.